Analisis Bauran Pemasaran Terhadap Minat Beli Kosmetik di The Body Shop (Studi Kasus pada Pengguna Produk The Body Shop di Mall Metropolitan Bekasi) - Irma Selliamanik; Gaby Valentine (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2023)
The purpose of this study is to analyze the effect of product, price, place, and promotion on buying intention. This research adopts quantitative methods. The sample of this research is the consumers cosmetics of The Body Shop who have made purchases on the Mall Metropolitan Bekasi for 100 respondents, using the purposive sampling technique. Methods of data collection using a questionnaire. This research data is processed using the Smart PLS 3 and SPSS version 25 Application. The results of this study partially show that the product and promotion variables have a significant effect on buying intention. Meanwhile the price and place variables has no significant effect on buying intention. But simultaneously all the variable, namely product, price, place, and promotion have a significant effect on buying intention.